Recurrent intermittent hyponatremia: A new experimental model - Marta Tejedor; Lorena Cussó; María Ángeles González-Nicolás; Diego San Felipe; Daniel Calle; Beatriz Martín-Sánchez; Baris Uzun; Giovanna Martín-Palumbo; Luis Antonio Alvarez-Sala Walther; Eva M. Marco; Meritxell López-Gallardo; Alberto Lázaro; et al. (PLoS ONE, 2026)
Aim It is assumed that natremia remains low throughout the duration of chronic hyponatremia, inducing symptoms. We explore Recurrent Intermittent Hyponatremia (RIH) to establish whether a few hours of hyponatremia per day are enough to induce significant water retention. Methods A rat model of RIH was developed and compared to control animals. Electrolyte balance and central nervous system (CNS) (water content and cellular changes) were studied at baseline and after a water overload equivalent to 10% of the animal’s body weight. Apparent diffusion coefficient (ADC) obtained through magnetic resonance was used to study changes in content and distribution of brain water. Immunohistochemistry techniques were used to study in the CNS astroglial cells through the glial fibrillary acidic-protein (GFAP) expression; as well as oligodendrocytes and the myelin sheath using the myelin basic protein (MBP) antibody. Blood and urine analysis were performed to assess water and electrolyte balance. Results In RIH, mild hyponatremia was induced, but recovered after 24h; this situation was repeated for 7 consecutive days. A lower ADC value in the whole brain compared to control animals suggested an increase in total brain water in this situation. An increase in GFAP expression in the gray matter (GM) was observed, while MBP’s expression remained unchanged. The water overload on RIH induced hypotonic hyponatremia, progressively decreased ADC values in the whole brain (less pronounced than in controls), and increased GFAP and MBP’s expression in the white matter (similar increase found in controls). Conclusion RIH is a novel animal model that suggests there can be significant water retention after only a few hours of hyponatremia a day provided this situation is repeated over time. Such water retention translates into a greater brain water accumulation and astroglial activation in the GM.